MOOCs for Second and Foreign Language Learners : Unpacking Critical Success Factors from the Pedagogical Perspective - Chuah, Kee Man; Xijing, Wang; Muhammad Kamarul, Kabilan (Penerbit USM, 2025)
The rise of massive open online courses (MOOCs) in the last decade has indeed offered a renewed interest in distance education. The flexibility of MOOC delivery has opened up opportunities for learners to learn any subject without being restricted to geographical or economic factors (Pappano, 2012; Baggaley, 2013). As compared to the traditional implementation of distance education, MOOCs capitalise on the advancement of internet and web technologies by creating a learning environment that is more user-friendly and offers greater access to global communication.